Dual-temperature dual-state fermentation: A novel approach to improve aroma and color characteristics of Marselan wines - Xuechen Yao; Haoen Cai; Jiayi Kou; Yunxue Xie; Jin Li; Penghui Zhou; Fei He; Changqing Duan; Qiuhong Pan; Mengyao Qi; Yibin Lan (Food Chemistry: X)
This study examined the effects of the Dual-Temperature Dual-State Fermentation (DTSF) technique on the chemical and sensory characteristics of industrial-scale ‘Marselan’ wine. Compared to the control wine, DTSF wine exhibited greater color intensity (chroma) attributed to higher levels of anthocyanin derivatives and copigments, along with a lower pH. Furthermore, DTSF wine retained higher concentrations of grape-derived aroma volatiles, including C6/C9 compounds, terpenoids, and norisoprenoids, and elevated levels of fermentation-derived esters (notably ethyl esters), contributing to a more intense fresh fruit aroma. Additionally, the DTSF technique had a minimal impact on condensed tannins and mouthfeel. This study confirms the viability of the DTSF technique for producing high-quality red wines and highlights its potential for the production of wines with diverse sensory profiles.